2008
DOI: 10.1080/02680930802262692
|View full text |Cite
|
Sign up to set email alerts
|

Policy rhetoric and the renovation of English schooling: the case of Creative Partnerships

Abstract: Facing difficulties in the implementation of its 'standards' agenda, the English government has recently introduced a set of policy strategies and initiatives which seek to promote enjoyment, innovation and creativity in education. One such initiative is Creative Partnerships (CP). Funded predominantly from the Arts portfolio, CP brings creative practitioners into schools with the intention of bringing change to teaching and learning, and, more widely, of achieving whole school change. Using a corpus of policy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 13 publications
0
20
0
1
Order By: Relevance
“…At the same time, an internal DfE memo revealed official changes in terminology from 11 May 2011, with ECM and the five outcomes to be replaced with 'help children achieve more' (Puffett 2010). Thus, as New Labour 'brands' (Jones and Thomson 2008), ECM and Extended Schools have been conspicuously dropped from national policy discourse, if not from policy, as the Children Act, for example, is still statutory at the time of writing. As former Labour Education Minister Estelle Morris asks, 'what's happening now?…”
Section: Study Supportmentioning
confidence: 97%
See 1 more Smart Citation
“…At the same time, an internal DfE memo revealed official changes in terminology from 11 May 2011, with ECM and the five outcomes to be replaced with 'help children achieve more' (Puffett 2010). Thus, as New Labour 'brands' (Jones and Thomson 2008), ECM and Extended Schools have been conspicuously dropped from national policy discourse, if not from policy, as the Children Act, for example, is still statutory at the time of writing. As former Labour Education Minister Estelle Morris asks, 'what's happening now?…”
Section: Study Supportmentioning
confidence: 97%
“…Theoretical framework and method This paper takes a policy analysis approach, informed by a perspective of policy as text/discourse, rather than a fixed entity, and policy formation as discursive practice (Ball 1993;Jones and Thomson 2008;Moss 2009) that can be contradictory and is re-made at different levels and over a period of time. My perspective is also influenced by Vidovich's (2007) 'hybridized policy cycle' framework, which focuses on the dynamic and context-specific relationship of macro-and micro-levels of policy processes.…”
Section: Study Supportmentioning
confidence: 99%
“…Funding supports creative practitioners, the majority of them artists, to work with teachers in redesigning curriculum, pedagogies, school cultures and structures (see Buckingham and Jones 2001;Thomson 2005, 2007;Jones and Thomson 2008). CPs ambition is to transform the practices of teaching and learning, and in so doing, change whole schools.…”
mentioning
confidence: 99%
“…A strand of research revealed tensions between the desire for widening access to creativity and centralised policies (Jones & Thomson, 2008 Troman et al, 2007) argued for the resolution of conflicts caused by the parallel agendas of creativity and performativity. Burnard and White (2008) argued that the performativity discourse in England was effectively hijacking the creativity discourse.…”
mentioning
confidence: 99%